Interactions between inflammatory mediators and corticosteroids regulate transcription of genes within the Kynurenine Pathway in the mouse hippocampus. Issue 1 (December 2016) - Brooks, Alexandra; Lawson, Marcus; Smith, Robin; Janda, Tiffany; Kelley, Keith; McCusker, Robert
Abstract Background Increased tryptophan metabolism towards the production of kynurenine via indoleamine/tryptophan-2, 3-dioxygenases (DOs: Ido1, Ido2, and Tdo2) is strongly associated with the prevalence of major depressive disorder in patients and the induction of depression-like behaviors in animal models. Several studies have suggested that activation of the immune system or elevated corticosteroids drive DO expression; however, mechanisms linking cytokines, corticosteroids, and DOs to psychiatric diseases remain unclear. Various attempts have been made to correlate DO gene expression within the brain to behavior, but disparate results have been obtained. We believe that discrepancies arise as a result of the under-recognized existence of multiple mRNA transcripts for each DO. Unfortunately, there are no reports regarding how the multiple transcripts are distributed or regulated. Here, we used organotypic hippocampal slice cultures (OHSCs) to directly test the ability of inflammatory and stress mediators to differentially regulate DO transcripts. Methods OHSCs were treated with pro-inflammatory mediators (interferon-gamma (IFNγ), lipopolysaccharide (LPS), and polyinosine-polycytidylic acid (pI:C)) with or without corticosteroids (dexamethasone (Dex: glucocorticoid receptor (GR) agonist), aldosterone (Aldo: mineralocorticoid receptor (MR) agonist), or corticosterone (Cort: GR/MR agonist)). Results IFNγ induced Ido1-full length (FL) and Ido1-variant (v) expression, and surprisingly, Dex, Cort, and Aldo interacted with IFNγ to further elevate expression of Ido1, importantly, in a transcript dependent manner. IFNγ, LPS, and pI:C increased expression of Ido2-v1 and Ido2-v3 transcripts, whereas only IFNγ increased expression of Ido2-v2. Overall Ido2 transcripts were relatively unaffected by GR or MR activation. Naïve mouse brain expresses multiple Tdo2 transcripts. Dex and Cort induced expression of only one of the three Tdo2 transcripts (Tdo2-FL) in OHSCs. Conclusions These results establish that multiple transcripts for all three DOs are expressed within the mouse hippocampus, under the control of distinct regulatory pathways. These data identify a previously unrecognized interaction between corticosteroid receptor activation and inflammatory signals on DO gene expression, which suggest that corticosteroids act to differentially enhance gene expression of Ido1, Ido2, and Tdo2.